The Value of Endoscopic Exposure of Round Window in Cochlear Implant via Facial Recess - Nassif, Mena Maher; Darahem, Islam Mohamed Hussein; Teaima, Ahmed Abdelmoneim; Mustafa, Mustafa Mohamed; Allah, Mohamed Saad Hassab; Ibrahim, Samer Ahmed (International Archives of Otorhinolaryngology, 2024)
Introduction Cochlear implantation has been considered as the best treatment in patients with severe to profound hearing loss unaidable with hearing aids. The main value of endoscope-assisted cochlear implantation is improved visibility of the RWObjective to assess the value of endoscopic assisted CI surgery via facial recess approach without elevating tympanic anulus.Methods This Prospective case series study non-randomized sample was performed on 50 patients with severe to profound hearing loss unaidable with hearing aids undergoing unilateral endoscopic assisted cochlear implant surgery with round window electrode insertionResults There were 23 male and 27 female patients. Most of the cases were children (41 cases). Of those 50 patients, 39 were prelingually hearing impaired. Four cases had various inner ear abnormalities. The standard mastoidectomy and Posterior Tympanotomy approach were used for all cases. Endoscopic identification of the RW through the PT enabled us to perform regular surgery in all cases. The current study concludes the difference between microscopic exposure and endoscopic exposure represented by Saint Tomas classification found that endoscopic exposure of round window classification is better represented by downgrading in the classification of round window exposure as type I 29(58%), type IIa 18(36%) type IIb 3 (6%) Non were type III by endoscopic exposure compared to microscopic exposure of round window is a type I 7(14%), type II 14(28%), type IIb 22(44%) and type III 7 (14%).Conclusion Endoscopy proved a great value in exposure and identification of RW in CI surgery through posterior tympanotomy approach,
Keywords: endoscopic-assisted CI; round window; endoscopic ear surgery